2023
DOI: 10.1371/journal.pntd.0010987
|View full text |Cite
|
Sign up to set email alerts
|

A long-term observational study of paediatric snakebite in Kilifi County, south-east Kenya

Abstract: Introduction Estimates suggest that one-third of snakebite cases in sub-Saharan Africa affect children. Despite children being at a greater risk of disability and death, there are limited published data. This study has determined the: population-incidence and mortality rate of hospital-attended paediatric snakebite; clinical syndromes of snakebite envenoming; and predictors of severe local tissue damage. Methods All children presenting to Kilifi County Hospital, Kenya with snakebite were identified through t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Children pose unique clinical challenges to clinicians treating SBE. In rural areas, children have a heightened propensity for snake encounters, as evidenced by the prevalence of up to one-third of reported cases in Nigeria and Australia [ 18 , 19 , 37 ] and 15% of reported snakebite cases in Brazil [ 38 ]. The reasons are most likely due to children’s playing activities, inquisitive nature, and lack of appreciation for the health risk associated with a snakebite.…”
Section: Paediatricsmentioning
confidence: 99%
See 3 more Smart Citations
“…Children pose unique clinical challenges to clinicians treating SBE. In rural areas, children have a heightened propensity for snake encounters, as evidenced by the prevalence of up to one-third of reported cases in Nigeria and Australia [ 18 , 19 , 37 ] and 15% of reported snakebite cases in Brazil [ 38 ]. The reasons are most likely due to children’s playing activities, inquisitive nature, and lack of appreciation for the health risk associated with a snakebite.…”
Section: Paediatricsmentioning
confidence: 99%
“…A study from Nigeria reported that children with cytotoxic SBE are more likely to need an amputation, blood transfusion, and antivenom than adults [ 19 , 40 ]. Antivenom is more commonly prescribed for children with snakebite than adults in sub-Saharan Africa, with the proportion ranging from 15–85% [ 13 , 15 , 18 , 19 , 20 ]. One study in India reported an odds ratio of 2.97 for a poor outcome (mortality, ventilation, or renal replacement therapy) in children under 5 years of age [ 13 ].…”
Section: Paediatricsmentioning
confidence: 99%
See 2 more Smart Citations